1996
DOI: 10.1161/01.cir.93.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Chronic Left Ventricular Dysfunction

Abstract: The results suggest that resting MBF measured with 15O-labeled water in chronically dysfunctional segments is not reduced and that the myocardium of these patients is less sensitive to insulin than that of normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Recent quantitative blood flow measurements have challenged the model of chronic myocardial underperfusion as the main cause of hibernating myocardium [5, 6, 7]. Marinho et al [7]found that chronic dysfunctional segments with functional recovery after revascularization had normal perfusion compared to remote normal contracting myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent quantitative blood flow measurements have challenged the model of chronic myocardial underperfusion as the main cause of hibernating myocardium [5, 6, 7]. Marinho et al [7]found that chronic dysfunctional segments with functional recovery after revascularization had normal perfusion compared to remote normal contracting myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Vanoverschelde et al [5]were the first who demonstrated that dysfunctional but noninfarcted collateral-dependent myocardium had normal myocardial blood flow as compared to remote myocardium. More recent studies in patients with chronic infarction confirmed that dyskinetic myocardium which recovered after revascularization had normal perfusion at rest [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that repetitive stunning of the type shown by us may result in chronic LV impairment. 28 Identification of clinically available therapeutic strategies that attenuate stunning and therefore lessen the impact of ischemia on LV function represent an important step in improving the medical management of patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…[10] However, studies of myocardial perfusion using positron emission tomography (PET) showed that myocardial blood flow in hibernating segments was normal, or near normal, in patients with left ventricular dysfunction due to coronary disease. [11,12] Even where myocardial blood flow was found to be reduced, the magnitude of decrease was insufficient to explain the severity of contractile dysfunction. [13] Myocardial hibernation is therefore now thought of as a form of chronic stunning.…”
Section: Pathophysiology Of Hibernating Myocardiummentioning
confidence: 99%